Conservative Management of Lateral Collateral Ligament Injury Due to Chiropractic Intervention In A Police Officer With Multiple Comorbidities: A Case Report - Pandhika, Radian; Priangga, I Kadek Rengkuh Wira Dana (Advances In Social Humanities Research, 2025)
A 56-year-old man, an active police officer, complained of acute pain and instability of the right knee. Medical history included an unoperated total rupture of the right anterior cruciate ligament (ACL) at the age of 23 years and grade 3 right genu osteoarthritis. Comorbidities included obesity (BMI 31.2 kg/m²), hypertension, dyslipidemia, hyperuricemia, and herniated nucleus pulposus (HNP). Physical examination revealed grade 1 right lateral collateral ligament (LCL) laxity, tenderness at the lateral joint line, limited range of motion, and crepitation. MRI confirmed right ACL rupture, right LCL sprain, medial meniscus tear, and grade 3 osteoarthritis. Conservative management included etoricoxib for pain, febuxostat for hyperuricemia, amlodipine for hypertension, rosuvastatin for dyslipidemia, anti-inflammatory herbal supplements, and omeprazole for gastrointestinal protection. Joint aspiration was performed to reduce effusion, and intra-articular Platelet-Rich Plasma (PRP) therapy was applied. The patient underwent a three-month physical rehabilitation program in three phases: initial, intermediate, and advanced. Therapeutic modalities included TENS, therapeutic ultrasound, gentle massage, muscle strengthening, proprioceptive, and aerobic exercises. The use of crutches and knee braces was reduced as joint stability and strength improved. During rehabilitation, patients showed significant progress: decreased pain, improved range of motion, muscle strength, and joint stability, and the ability to return to professional activities. The comprehensive approach and interdisciplinary collaboration enabled optimal functional recovery despite the presence of comorbidities and complex medical history.